Cover Feature: Nitride‐Derived Copper Modified with Indium as a Selective and Highly Stable Catalyst for the Electroreduction of Carbon Dioxide (ChemSusChem 15/2019). Issue 15 (1st August 2019) - Veenstra, Florentine L. P.; Martín, Antonio J.; Pérez‐Ramírez, Javier
Abstract : The Cover Feature shows how microfabrication enables excellent stability and activity for the electrocatalytic reduction of carbon dioxide on particulate indium oxide supported on copper nitride. Patterned indium oxide islands deposited over the benchmark copper oxide (right) revealed the diffusion of indium into the copper support under reaction conditions as the cause for its unstable performance. In contrast, this process is hindered on copper nitride (left), resulting in a material with highly stable and active In–Cu interphases. More information can be found in the Full Paper by F. L. P. Veenstra et al. on page 3501 in Issue 19, 2015 (DOI: 10.1002/cssc.201901309 ).